2007
DOI: 10.1159/000102303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>L</i>-Carnitine and Propionyl-<i>L</i>-Carnitine on Endothelial Function of Small Mesenteric Arteries from SHR

Abstract: Background:The effect of treatment with either 200 mg·kg–1 of L-carnitine (LC) or propionyl-L-carnitine (PLC) was studied on endothelial dysfunction of small mesenteric arteries (SMA) from spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) rats. Methods: Systolic blood pressure (SBP) was measured and endothelial and vascular functions were assessed by the effect of carbachol (CCh) and phenylephrine (Phe). O2 produced by SMA and eNOS expression were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 65 publications
5
32
0
Order By: Relevance
“…The decrease in the presence of O 2 − in SHRs appears to be specific to the cerebral vasculature as, in third-order MRAs from age-matched rats, basal O 2 − was increased in SHRs instead. These findings are in accordance with several other studies performed in both conduit [40,41] and resistance [42] arteries from this strain.…”
Section: Discussionsupporting
confidence: 94%
“…The decrease in the presence of O 2 − in SHRs appears to be specific to the cerebral vasculature as, in third-order MRAs from age-matched rats, basal O 2 − was increased in SHRs instead. These findings are in accordance with several other studies performed in both conduit [40,41] and resistance [42] arteries from this strain.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, it has been reported that L-carnitine was able to improve the endothelium-dependent relaxation of small mesenteric arteries from SHR by decreasing vascular O 2 − production, thus increasing NO participation in endothelial function. [26] These findings indicate that vasodilatation and the enhancement of renal perfusion contributed, at least in part, Data shown above are the mean ± SD. All parameters were determined in the rats that were killed at 96 hours.…”
Section: Discussionmentioning
confidence: 82%
“…Under our experimental conditions, MRA from SHR exhibited a biphasic response to ACh, whereas in WKY only a vasodilator component was observed. The contractile component was maintained after NO and EDHF blockade and has been previously demonstrated to be due to the effect of cyclooxygenase (COX)-derived prostanoids and/or free radicals released at high concentrations of ACh in SHR MRA, which are not produced in the WKY strain (2,30,69).…”
Section: Discussionmentioning
confidence: 93%
“…However, the present and previous data let us suggest that it can be linked to an antioxidant effect. First, LGF was able to reduce the elevated superoxide anion levels in SHR MRA, which is a common feature in several vascular beds from SHR (2,34). We have previously demonstrated that LGF exerts potent in vitro scavenging capacity against several ROS, including superoxide anion and hydroxyl and peroxyl radicals (18).…”
Section: Possible Mechanism Of Action Of Lgfmentioning
confidence: 96%
See 1 more Smart Citation